Electro-magneto flow of nanomaterial with irreversibility. (April 2020) - Ijaz Khan, M.; Khan, Sohail A.; Hayat, T.; Imran Khan, M.; Alsaedi, A.
Highlights: Entropy optimization in electrical magnetohydrodynamic mixed convective flow is discussed. Energy equation is discussed in the presence of Joule heating, heat source/sink and viscous dissipation. Chemical reaction is also considered at the surface. Total entropy optimization rate is calculated. Abstract: Here we discuss the analysis of irreversibility in electrical magnetohydrodynamic convective flow of nanomaterials over a stretchable surface. Energy equation deliberated through Joule heating, dissipation and heat source/sink. Furthermore features chemical reaction is also considered. Total entropy optimization is calculated. Salient features of thermophoresis effect and random motion of particles are studied. Nonlinear couple equations are converted to ordinary system by using the transformation. The obtained system are elucidated through ND solve technique. Salient features of pertinent variables on entropy optimization, velocity, Bejan number, concentration and temperature are discussed. Nusselt number, gradient of concentration and surface drag force are computationally calculated. Velocity and temperature show opposite behaviors via magnetic parameter. Electric and magnetic field parameters on entropy optimization have opposite results.